The Size Structure and Growth Pattern of Squid (Loligo sp.) in Majene Waters, West Sulawesi Province - Alam Nasyrah, Adiara Firdhita; Hudriyah Idris; Eva Muhajirah; Anna Heirina (Jurnal Moluska Indonesia, 2024)
Squid belongs to the phylum Mollusca, specifically the Cephalopoda group (soft-bodied animals) which is one of Indonesia's fisheries resources. One of the regions abundant in squid fisheries resources is the waters of Majene, West Sulawesi Province. This research aims to determine the distribution of the captured squid's size structure and growth patterns in the waters of Majene. Squid sampling was conducted in July–August 2023. The sampling procedure involved randomly selecting squid catches from fishermen in the waters of Majene with a sampling frequency of once a month, resulting in a total of 102 specimens of Loligo sp. squid, consisting of 82 males and 20 females. Overall, the range of mantle length obtained for Loligo sp. squid was 90–180 mm, with a weight range of 26.08–306.19 g. The majority of male squid caught during the study had a mantle length in the range of 127–138 mm, while female squid had a mantle length range of 115–126 mm. Based on statistical analysis, the growth pattern of combined and male Loligo sp. squid in the waters of Majene exhibited negative allometric growth, meaning that weight increase was more dominant than length increase. In contrast, female squid exhibited positive allometric growth, indicating that weight increase was more dominant than length increase.